(untitled) (Orinoquia, 2010)
Abstract: With the approval of the National Education Ministry of three new master’s programs (sustainable environmental management, sustainable tropical agricultural production and Sustainable Systems of Tropical Animal Health and Production) in addition to the existing expertise in aquaculture, La Universidad de Los Llanos is on its way to face the great changes coming in the region.